Liikuntalääketieteen poliklinikan toteuttaman hoidon vaikutus lihavuuspotilaiden elämänlaatuun - Saarinen, Veera (2024)
Obesity is associated with several health consequences such as an increased risk of many chronic diseases as well as reduced health-related quality of life (HRQoL). Increasing exercise is one of the most important lifestyle modifications related to obesity treatment. Regular exercise has shown beneficial effects on weight loss and weight management, cardiorespiratory fitness and general well-being. The purpose of this registry-based study was to find out if individual exercise therapy is effective on health-related quality of life of obese patients as measured by the RAND-36 Item Health Survey. In addition, the results were examined in groups between those who increased exercise during the treatment and those who did not. It was also examined whether quality of life changes were associated with weight changes. The data was collected from the patient records of the Sports and Exercise Medicine Clinic of Hospital Nova in the wellbeing services county of Central Finland. The data was collected for those obese (BMI ≥ 30 kg/m²) patients who had completed RAND-36 quality of life questionnaire at the beginning and end of exercise therapy (n=15). The data was analyzed with the IBM SPSS Statistics 28 program. Wilcoxon signed rank test and Mann-Whitney U test were used as the analysis methods to examine the change in quality of life in entire data and between those who increased exercise and those who did not. The association between quality of life and weight changes was examined using Spearman’s rank correlation coefficient. Individual subscales of RAND-36 were used as variables describing quality of life, as well as the sum variables (physical and mental health-related quality of life) formed from them. During the follow-up, well over half of the participants successfully increased their exercise (57 %). No statistically significant differences were found between the initial and final measurements when the entire data was analyzed (n=15). After removing outliers, mental HRQoL improved statistically significantly between initial and final measurements (n=13, Z=-2.041, p=0.039, r=0.40). Removal of outliers did not affect the statistical significance of the physical HRQoL or individual RAND-36 subscales. No significant differences in quality of life measures were found between those who increased exercise and those who did not. Changes in quality of life were also not significantly related to changes in weight. During an average of 14 months of follow-up, individual exercise therapy was successful in increasing physical activity in patients who did not exercise regularly before participating this study. Exercise therapy also had a positive effect on mental HRQoL. However, the improvement in quality of life did not depend on successful increase in exercise or changes in weight. The results of the study should be interpreted with caution, as the data was small and not all confounding factors such as serious mental health illness or other concurrent treatment, could be accounted for. Further research on the subject will be done when more data is available in the outpatient Sports and Exercise Medicine Clinic.